1990
DOI: 10.1007/bf00764672
|View full text |Cite
|
Sign up to set email alerts
|

Exafs study of the local structure of Ni in Ni-MoS2/C hydrodesulfurization catalysts

Abstract: To study the local structure of the Ni promoter atom, the Ni and Mo K edge EXAFS spectra of Ni-MoSz/C hydrodesulfurization catalyst were measured in an in-situ EXAFS cell at 77 K. The Ni atom is situated in a square pyramid of five S atoms at a distance of 2.21 from the S atoms. In addition an EXAFS contribution due to a Mo atom at 2.82 A from the Ni atom could be identified. This local structure indicates that the Ni atoms are situated on top of the S 4 squares at the MoS 2 edges in millerite-type Ni sites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 26 publications
9
31
0
Order By: Relevance
“…It is obvious in this figure that the Co-S peak amplitude increases in the order: Co9S 8 < Co/C < Co-Mo/C. Data-analysis (including the influence of Debye-Waller factors) reveals that the Co-S coordination number increases in the same order [11]. From these spectral characteristics it is immediately clear that the cobalt ions in the catalysts have a higher sulfur coordination than those in Co9S 8 and furthermore, that this phenomenon is more pronounced when cobalt is present in a Co-Mo-S structure.…”
mentioning
confidence: 85%
“…It is obvious in this figure that the Co-S peak amplitude increases in the order: Co9S 8 < Co/C < Co-Mo/C. Data-analysis (including the influence of Debye-Waller factors) reveals that the Co-S coordination number increases in the same order [11]. From these spectral characteristics it is immediately clear that the cobalt ions in the catalysts have a higher sulfur coordination than those in Co9S 8 and furthermore, that this phenomenon is more pronounced when cobalt is present in a Co-Mo-S structure.…”
mentioning
confidence: 85%
“…Up to now, numerous experimental techniques have been employed to better characterize the catalytically "CoMoS" or "NiMoS" active phases [2,3]. Experimental techniques involved in the characterization of these complex phases consist of transition electron microscopy (TEM) [4,5], X-ray photoelectron spectroscopy (XPS) [6][7][8][9], Mössbauer spectroscopy [10][11][12], laser Raman spectroscopy [5,13], extended X-ray absorption fine structure (EXAFS) [14][15][16][17][18], and IR spectroscopy [19,20]. These techniques furnished many detailed features of the so-called Co(Ni)MoS active phase made of MoS 2 layers with a stacking close to 1 [21] and nanometer sizes (less than 30 Å), "decorated" by Co or Ni at the edges.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques furnished many detailed features of the so-called Co(Ni)MoS active phase made of MoS 2 layers with a stacking close to 1 [21] and nanometer sizes (less than 30 Å), "decorated" by Co or Ni at the edges. While Mössbauer spectroscopy [10][11][12] and XPS [6][7][8][9] revealed the specific signature of Co atoms engaged in the new CoMoS phase, EXAFS gave relevant insights into the local environment of the promoter atoms (Co or Ni) in the structure [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the Ni(0.5) series of catalysts the ratio Ni/Mo = 0.24 is low enough for all Ni to end up in the Ni-Mo-S phase. This expectation is based on 57Co M6ssbauer emission spectroscopic work on the analogous Co-Mo system (49,53) and on the results of an EXAFS investigation of a series of Ni-Mo catalysts, which showed that at a Mo loading of about 7% Ni3S 2 could only be observed for Ni/Mo > 0.5 (54). This expectation is also corroborated for Ni-Mo-P/A1203 catalysts.…”
Section: Discussionmentioning
confidence: 74%
“…Another point is that the type IIMoS 2 crystallites are larger than the type I crystallites (49), since the former type is generated from molybdenum oxide in weak interaction with the support. As a consequence, the more type II is present, the more Ni will be forced to segregate as nickel sulfide (presumably Ni3S 2 (54)). In the P-containing catalysts not only the interaction between molybdate and support will be weaker, but also, because phosphate decreases the support surface area (cf.…”
Section: Discussionmentioning
confidence: 99%